(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This article is a critical commentary on the behavior analytical tradition regarding its attempts to deal with and interpret social phenomena and problems, focusing mainly on the choice for research questions that could lead to ‘revolutions’ both in the way we interpret such phenomena, and also by sparking broader social changes. We explored broader contexts controlling and informing behavior analysts’ choices, and pro-vided examples. The present paper suggests that, in order to promote social changes toward a more egalitarian society while using behavior analysis, researchers and practitioners should examine more thoroughly their own decisions on which knowledge sources must be considered when taking action upon our society. Furthermore, the interpretation presented advocates for a radical social analysis of social phenomena, in agreement with radical behaviorism and contextual analysis. Such analysis should take into consideration the knowledge already produced or in production by the population that will participate in it.